Too young to pour: the global crisis of underage alcohol use - Susanna Esposito; Beatrice Rita Campana; Alberto Argentiero; Marco Masetti; Valentina Fainardi; Nicola Principi (Frontiers in Public Health)
BackgroundUnderage alcohol consumption remains a critical global public health concern, contributing to a wide spectrum of short- and long-term health risks. Despite age-based legal restrictions, alcohol persists as the most commonly used psychoactive substance among minors, outpacing tobacco, cannabis, and other drugs. Early initiation of alcohol use is strongly associated with heightened risks of addiction, impaired brain development, mental health disorders, and engagement in high-risk behaviors such as unintentional injuries, violence, and academic underperformance. Most research has focused on adolescents, while data on younger children remain scarce. Moreover, methodological inconsistencies in defining and measuring alcohol use across countries complicate international comparisons and the evaluation of policy interventions.MethodsThis narrative review synthesizes contemporary literature on the epidemiology, determinants, and consequences of underage alcohol use. It examines genetic predispositions, family dynamics, peer influence, socioeconomic context, mental health, and exposure to alcohol-related media and advertising. It also evaluates the effectiveness of intervention strategies, including parental engagement, school-based education, extracurricular activities, community-level regulation, and professional health services.ResultsEvidence highlights significant variability in the prevalence of underage drinking across regions, influenced by cultural, legal, and socioeconomic factors. Parental modeling, permissive attitudes, and weakened family structures are major contributors, while peer pressure and media exposure further normalize early alcohol use. Although various prevention strategies have demonstrated short-term benefits (particularly those involving active parental involvement and skill-based school programs), long-term effectiveness is limited due to inconsistent implementation, lack of standardization, and inadequate policy enforcement. Community-level interventions, such as increasing the legal drinking age and conducting compliance checks, have shown measurable success, but are underutilized in many regions.ConclusionAddressing underage drinking requires a coordinated, multifactorial strategy. Broader investment in early prevention, standardized assessment tools, and targeted research on younger populations is essential. Strengthening policy enforcement and cross-sector collaboration will be critical to mitigate this growing public health challenge.